A survey on management practices of hypotension in preterm neonates: an Indian perspective - Das, Rupam; Nagpal, Rema; Deshpande, Sujata; Kumar, Gunjana; Singh, Anita; Kallimath, Aditya; Suryawanshi, Pradeep (Frontiers in Pediatrics, 2024)
Background: Hypotension is a common entity in the neonatal intensive care unit (NICU) and is reported in 24-50% of preterm infants with birth weight less than 1500 g. Rapid diagnosis and aggressive management is crucial to reduce its detrimental effects on end-organs especially the brain. Physicians often rely on blood pressure alone as a reliable indicator of tissue perfusion, but variations exist in the definition of this crucial parameter. There are also practice variations in the use of diagnostic tools and management modalities among physicians.A physician-based cross-sectional survey of management practices of hypotension in preterm neonates in Indian NICUs was conducted using an online survey tool.The questionnaire addressed diagnostic criteria used, utility of echocardiography for the assessment of hypotension, and management strategies used, such as volume expansion, inotropes and steroids.Results: Three hundred and twenty physicians, working predominantly in Level III NICUs, responded to the survey. The practice of delayed cord clamping was followed in the units of 78% respondents. Only 44% respondents had an institutional written protocol for the management of hypotension. The criteria for the diagnosis of hypotension varied, with 52% using mean blood pressure (BP) less than gestational age as the criteria. Capillary refill time, blood pressure and heart rate were the most common clinical criteria used. 85% respondents used echocardiography in the NICU, but only 73% utilised it for assessment of a hypotensive neonate. Physicians preferred a 'volume-inotrope-echo-steroid' strategy, with 85% respondents using volume expansion. Dopamine was the preferred first line inotrope, followed by norepinephrine and low-dose epinephrine.This survey reflects significant variations in practice amongst neonatal physicians in India. Bedside targeted echocardiography needs to be better utilised as a vital tool to determine the pathophysiology of disease and hemodynamic monitoring in the management of hypotension in neonates. While further research is needed on outcome-oriented objectives, awareness and dissemination of already existing guidelines would be useful to standardize clinical practice.